2002
DOI: 10.1053/jhep.2002.35540
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of direct lineage between hepatocytes and hepatocellular carcinoma in diethylnitrosamine-treated rats

Abstract: The question whether hepatocellular carcinoma (HCC) arises from dedifferentiation of mature hepatocytes or from proliferation of liver stem cells is still debated. In the present study, we used retroviral-mediated genetic labeling to investigate the fate of mature hepatocytes in rats after administration of diethylnitrosamine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 26 publications
(33 reference statements)
1
44
0
Order By: Relevance
“…There are two major nonexclusive hypotheses of the cellular origin of cancer: from stem cells due to maturation arrest or from dedifferentiation of mature cells. Debate has centered on whether hepatocytes are responsible for HCCs through dedifferentiation, or whether oval cells are the prime target for malignant changes after a differential "block" [3,5] . Oval cells are possibly involved in hepatocarcinogenesis based on the followings: (1) massive existence of oval cells in an animal rodent hepatocarcinogenic model [28] ; (2) development of HCC after transformation of oval cells [8] ; and (3) occurrence of mixed hepatocellular and cholangiocarcinomatous tumors (oval cell exhibits bipotential developmental ability) [29] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two major nonexclusive hypotheses of the cellular origin of cancer: from stem cells due to maturation arrest or from dedifferentiation of mature cells. Debate has centered on whether hepatocytes are responsible for HCCs through dedifferentiation, or whether oval cells are the prime target for malignant changes after a differential "block" [3,5] . Oval cells are possibly involved in hepatocarcinogenesis based on the followings: (1) massive existence of oval cells in an animal rodent hepatocarcinogenic model [28] ; (2) development of HCC after transformation of oval cells [8] ; and (3) occurrence of mixed hepatocellular and cholangiocarcinomatous tumors (oval cell exhibits bipotential developmental ability) [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, DEN (Sigma) was continuously administered for 12 wk through drinking water at a final concentration of 100 μg/L to induce hepatocarcinogenesis [3] .…”
Section: Diethylnitrosamine(den)-induced Hepatocarcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…To further examine the role of E-cadherin in hepatocarcinogenesis, we used diethylnitrosamine (DEN) to induce a hepatocyte-derived HCC [ 9 ]. CDH1 F/F mice and CDH1 Δ L mice were injected with 25 mg/kg DEN on postnatal day 14 [ 10 ].…”
Section: Loss Of E-cadherin Promotes Chemical-induced Hccmentioning
confidence: 99%
“…This was established by stably labelling hepatocytes at 1 day after a two-thirds PH with β-galactosidase, using a recombinant retroviral vector containing the β-galactosidase gene; subsequent feeding with 2-acetylaminofluorene led to foci, some of which were composed of β-galactosidaseexpressing cells. Using the same labelling protocol, Bralet et al [135] observed that 18% of hepatocytes expressed β-galactosidase at the completion of regeneration after a two-thirds PH; subsequent chronic treatment with diethylnitrosamine (DEN) resulted in many HCCs, of which 17.7% of the tumours expressed β-galactosidase, leading to the conclusion that a random clonal origin of HCC from mature hepatocytes was operative in the model.…”
Section: Mr Alison Et Almentioning
confidence: 99%